Impact of Close Margins in Head and Neck Mucosal Squamous Cell Carcinoma: A Systematic Review. (18th June 2021) - Hamman, Justin; Howe, Carol L.; Borgstrom, Mark; Baker, Audrey; Wang, Steven J.; Bearelly, Shethal
Abstract : Objectives/Hypothesis: The aim of the study is to investigate whether close surgical margins impact oncologic outcomes compared to clear or involved surgical margins. We hypothesize that close surgical margins portend worse outcomes compared with clear margins, but improved outcomes compared with involved margins. Study Design: Systematic review. Methods: Using the Preferred Reporting Items for Systematic Reviews and Meta‐analysis statement standards, a systematic search was conducted for studies that reported oncologic outcomes following excision of primary mucosal head and neck squamous cell carcinoma (HNSCC). A meta‐analysis was then performed, comparing local recurrence (LR), locoregional recurrence (LRR), and overall survival (OS) in patients with clear, close, and involved margins. Results: Twenty‐six studies met the inclusion criteria, totaling 8, 435 patients. About 96% of our included cases involved the oral cavity, 2% involved the oropharynx, and 2% other. Also, 68% of cases were T1/T2 and 32% were T3/T4. On meta‐analysis, clear margins were associated with lower incidence of 5‐year LR relative risk (RR) 0.50, 95% confidence interval [CI] 0.38–0.65) and higher 5‐year OS (RR 1.22, 1.11–1.35), when compared with close margins. Involved margins had higher incidence of 5‐year LR (RR 1.75, 1.16–2.64), higher incidence of LRR at last follow‐up (RR 1.66, 1.37–2.00), and no difference in 5‐year OS (RR 0.82, 0.60–1.11), when compared with close margins. Conclusions: There is a stepwise improvement in oncologic outcomes as surgical margin categorically improves from involved to close to clear. Patients with close margins therefore may benefit from adjuvant therapy. Further research is required to investigate whether these findings are seen in non‐oral cavity cases because they were underrepresented in this analysis. Laryngoscope, 132:307–321, 2022